2013
DOI: 10.1093/cid/cit002
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Causes of Suboptimal Response to Tenofovir-Based Therapy in Individuals Coinfected With HIV and Hepatitis B Virus

Abstract: Tenofovir/emtricitabine was superior to other anti-HBV regimens in long-term HBV suppression. HBV viremia on therapy was identified in 1 of 3 main patterns. Suboptimal adherence was associated with detectable HBV DNA during therapy, even when HIV was undetectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
50
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 14 publications
(20 reference statements)
14
50
1
1
Order By: Relevance
“…Baseline CD4 + T cells were significantly associated with HBV DNA suppression at 12 months but not at other visits. This concurs with other studies such as Kim et al [43] who reported baseline CD4 + T cells as a predictor of HBV suppression in response to tenofovir [44]. …”
Section: Discussionsupporting
confidence: 93%
“…Baseline CD4 + T cells were significantly associated with HBV DNA suppression at 12 months but not at other visits. This concurs with other studies such as Kim et al [43] who reported baseline CD4 + T cells as a predictor of HBV suppression in response to tenofovir [44]. …”
Section: Discussionsupporting
confidence: 93%
“…We also found that drug-resistant HBV only emerged in those on lamivudine or emtricitabine monotherapy, which is consistent with data showing no resistance with TDF-based therapy [22, 28, 29]. …”
Section: Discussionsupporting
confidence: 90%
“…No other anti-HBV agents were associated with intrahepatic viral loads with the exception of significantly higher total IH-DNA in univariable analysis after 3-6 years of cumulative LAM-exposure, most likely due to the presence of LAM-resistance. These observations bolster previous works among HIV-HBV co-infected patients where similar conclusions were reached using plasma HBV-DNA levels [18][19][20]. Nevertheless, the data presented here allow a more thorough understanding of how these factors are associated with activity in the liver, which is not necessarily the case when measuring circulating HBV-DNA levels [21].…”
Section: Discussionsupporting
confidence: 86%